2023
DOI: 10.1038/s42003-023-04665-w
|View full text |Cite
|
Sign up to set email alerts
|

CCR3 plays a role in murine age-related cognitive changes and T-cell infiltration into the brain

Abstract: Targeting immune-mediated, age-related, biology has the potential to be a transformative therapeutic strategy. However, the redundant nature of the multiple cytokines that change with aging requires identification of a master downstream regulator to successfully exert therapeutic efficacy. Here, we discovered CCR3 as a prime candidate, and inhibition of CCR3 has pro-cognitive benefits in mice, but these benefits are not driven by an obvious direct action on central nervous system (CNS)-resident cells. Instead,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Furthermore, we validated the impact of CCR3 inhibition on the recruitment of T cells in the MOG model (Fig 5). These results are consistent with the observed effects of CCR3 inhibition by AKST4290 in reducing the number of T cells in the brain in the MOG model [23].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, we validated the impact of CCR3 inhibition on the recruitment of T cells in the MOG model (Fig 5). These results are consistent with the observed effects of CCR3 inhibition by AKST4290 in reducing the number of T cells in the brain in the MOG model [23].…”
Section: Discussionsupporting
confidence: 91%
“…An immune reaction was generated against myelin with M. Tuberculosis H37 Ra and pertussis toxin in a similar fashion to experimental autoimmune encephalomyelitis (EAE) induction [25]. On an abbreviated time course, in comparison to EAE, this technique has been shown to robustly mobilize T cells to myelin containing regions such as the CNS and we refer to this model as MOG (myelin oligodendrocyte glycoprotein) [23]. Thus the MOG model does not recapitulate AMD but rather allows for validation of the robust effect CCR3 inhibition has on a specific feature of the immune response in AMD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, other studies have found that aged microglia in the subventricular zone upregulate Ccl5 and Ccl2 to recruit CCR3-expressing T cells (13). Inhibiting CCR3 in T cells attenuates this T-cell migration into the brain and alleviates microgliosis in aged mouse brains (14). In line with current literature, previous work in our laboratory indicated that microglia from aged mouse brains demonstrate more significant levels of activation after TBI than microglia from young mouse brains after TBI (6).…”
Section: Introductionssupporting
confidence: 75%